Challenging Encounters and Within-Physician Practice Variability - Gabriel Chodick; Yoav Goldstein; Ity Shurtz; Dan Zeltzer (Institute of Labor Economics (IZA), 2022)
We examine how physician decisions are impacted by difficult cases—encounters with newly diagnosed cancer patients. Using detailed administrative data, we compare primary care physicians' decisions in visits that occurred before and after difficult cases and matched comparison cases by the same physicians on other dates. Immediately following a difficult case, physicians increase referrals for common tests, including diagnostic tests unrelated to cancer. The effect lasts only for about an hour and is not driven by patient selection or schedule disruption. The results highlight difficult encounters as a source of variability in physician practice.
Keywords: I1; D91; 330; primary care; practice variation; intra-rater reliability